2018
DOI: 10.1371/journal.pone.0195577
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological mechanisms of vandetanib-induced cardiotoxicity: Comparison of action potentials in rabbit Purkinje fibers and pluripotent stem cell-derived cardiomyocytes

Abstract: Vandetanib, a multi-kinase inhibitor used for the treatment of various cancers, has been reported to induce several adverse cardiac effects. However, the underlying mechanisms of vandetanib-induced cardiotoxicity are unclear. This study aimed to investigate the mechanism of vandetanib-induced cardiotoxicity using intracellular electrophysiological recordings on human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs), rabbit Purkinje fibers, and HEK293 cells transiently expressing human ether-a-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
(33 reference statements)
2
13
0
1
Order By: Relevance
“…In this study, we demonstrated that vandetanib prolonged the QT interval in Langendorff perfusion rabbit hearts. Also, vandetanib can prolong the cardiac action potential in rabbit heart and hiPSC-CMs, which are consistent with the results reported in the literature [ 22 ]. Malignant arrhythmias caused by QT interval prolongation pose a serious threat to patient's life safety and then limit their clinical application.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we demonstrated that vandetanib prolonged the QT interval in Langendorff perfusion rabbit hearts. Also, vandetanib can prolong the cardiac action potential in rabbit heart and hiPSC-CMs, which are consistent with the results reported in the literature [ 22 ]. Malignant arrhythmias caused by QT interval prolongation pose a serious threat to patient's life safety and then limit their clinical application.…”
Section: Discussionsupporting
confidence: 92%
“…However, 24-74% of routinely prescribed drugs have the potential to interact with cytochrome P450 3A4 metabolism, which can result in increased toxicity. Indeed, vandetanib has been shown to bind directly to cardiomyocyte hERG potassium channels in vitro and to inhibit potassium and sodium currents, resulting in attenuated depolarisation and delayed action potentials [75].…”
Section: Multi-target Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Most reports on the RMP and AP waveform of hSC-CMs and hiPSC-CMs present data from isolated cells that were dissociated from their monolayers or 3D structured cultures 4 to 10 days prior to the measurements [13,[44][45][46][47]. On the other hand, native CMs are mostly recorded immediately after dissociation, as longer culturing of these cells leads to more depolarized RMP values and larger AP waveform variability [48].…”
Section: Discussionmentioning
confidence: 99%